Pengaruh Pembinaan Disiplin dan Motivasi Kerja Terhadap Kepuasan Kerja Pegawai Bank XYZ Cabang Cimahi - Dwitiara Siregar, Adha Aulia; Mulyana, Aam Rachmat (Fakultas Ekonomi dan Bisnis, Universitas Jenderal Achmad Yani, 2025)
The increase in employee turnover at Bank XYZ Cimahi Branch in 2023 reaching 17,5% is a problem that must be studied. This research aimed to assess the effects of disciplinary coaching (X1) and work motivation (X2) on employee job satisfaction at Bank XYZ Cimahi Branch Office, both simultaneously and partially. The researcher used a quantitative methodology, including data gathering approaches including documentation, questionnaires, and interviews. Respondents in this study were 65 employees. Multiple linear regression analysis using the SPSS 27.0 software was the method of data analysis used. The findings of this study show that partially discipline coaching has a positive impact on employee job satisfaction at Bank XYZ Cimahi Branch Office, and work motivation has a positive effect on employee job satisfaction at Bank XYZ Cimahi Branch Office. Discipline coaching and work motivation simultaneously have an impact on employee job satisfaction at Bank XYZ Cimahi Branch Office which is included in the high/strong influence criteria. With the conclusion that the higher the discipline coaching and work motivation, the higher the employee job satisfaction at Bank XYZ Cimahi Branch Office.